Energy use in open-field agriculture in the EU: A critical review recommending energy efficiency measures and renewable energy sources adoption. (April 2022) - Paris, Bas; Vandorou, Foteini; Balafoutis, Athanasios T.; Vaiopoulos, Konstantinos; Kyriakarakos, George; Manolakos, Dimitris; Papadakis, George
Abstract: This review combines results from a large number of studies investigating energy use in EU open-field agriculture, providing an overview of energy use and its concentrations. Such a review and its findings are important as it informs stakeholders and policymakers with evidence for supporting a green energy transition in open-field agriculture. Our review indicates that annual energy use in EU open-field agriculture is at least 1431 PJ, equivalent to around 3.7% of total EU annual energy consumption, with the majority of energy sourced from non-renewable energy sources. Our meta-analysis finds that the production of fertilizer is the largest energy consuming activity in EU agriculture, accounting for around 50% of all energy inputs. On-farm diesel use accounts for 31% of total energy inputs, while the production pesticides and seeds accounts for 5% of total energy inputs. Other energy uses, mainly irrigation, storage and drying, account for 8% of total energy inputs. This suggests that energy use in EU agriculture is significantly underreported and that around 55% of total energy inputs, associated with the production of fertilizers and pesticides, come from indirect sources which can be assigned to the agricultural sector but is used prior to reaching farms. The importance and potential of various fossil-energy-free technologies and strategies are discussed. In addition, this review highlights that in the medium and long term there is need for the development and application of detailed and standardized methodologies for energy use analysis of agricultural systems, as well as for meta-analyses investigating energy use in agriculture. Highlights: Energy use in EU open-field agriculture is at least 1431 PJ. On-farm diesel use accounts for 31% of total energy inputs. 55% of total energy inputs in open-field EU agriculture come from indirect sources. Fossil-energy-free technologies and strategies will support a green transition. Sustainable fertilizers and pesticides can reduce indirect fossil energy use.